Răspuns :
z:(-19)=-18
z:(-19)-(-18)=0
simplificam ....z
-------
-19
z
------ - -18=0
-19
-18 -18 *-19
- 18= ---------- = --------------
1 -19
z*- 1 - (-18*19) 342 - 2
-------------------- = -----------
19 19
342-2
-------- = 0
19
342 - 2
---------- *19 =0*19
19
342-z=0
-2+342=0
-2= -342
(-1):z=342
z=342
342:(-19)=-18
z:(-19)-(-18)=0
simplificam ....z
-------
-19
z
------ - -18=0
-19
-18 -18 *-19
- 18= ---------- = --------------
1 -19
z*- 1 - (-18*19) 342 - 2
-------------------- = -----------
19 19
342-2
-------- = 0
19
342 - 2
---------- *19 =0*19
19
342-z=0
-2+342=0
-2= -342
(-1):z=342
z=342
342:(-19)=-18